Control of Partheniumhysterophorus (L) and its Impact on Yield Performance of Tomato (Solanum lycopersicum L) in the Northern Province of Sri Lanka - Nishanthan, K.; Sivachandiran, S.; Marambe, B. (Tropical Agricultural Research 25, 2013)
Impact of weed control methods on the persistence of Partheniumhysterophorus (L), and quantity and quality of tomato (Solanum lycopersicum L) yield was studied in two farmer fields i.e. a site heavily infested with P. hysterophorus (Parthenium-site) and Parthenium-free site, in the Jaffna peninsula of the Northern Province of Sri Lanka. The split-plot design consisted of two main plots i.e. manual weeding and ploughing (both followed by harrowing), and three sub-plots i.e. use of a pre-emergent herbicide (Oxyfluorfen; 240 g/L EC at 2 days before planting), mulching [Gliricidiasepium (Jacq) Kunth ex Walp. leaves at 12 kg per plot on fresh weight basis], and un-weeded plot after crop establishment (control), in three replicates. The soil seed bank of the Parthenium-site was dominated by P. hysterophorus as expected, and the Parthenium-free site was dominated by the perennial sedge Cyperusrotundus (L). At tomato harvest, the un-weeded sub-plots recorded the highest weed densities (p<0.05) when compared to the rest, The Parthenium-site showed a higher weed dry weight (p<0.05) when compared to that of the Parthenium-free site, due to higher emergence of the Parthenium weed in the former. Mulching was the best sub-plot treatment for Parthenium control in combination with the main plot treatments. The average fruit weight of tomato at the Parthenium-free site was 7.8% higher than that of the Parthenium-site (47.8 g per fruit). In the Parthenium-site, mulching resulted in a 6.4% higher fruit weight and 58% higher total yield (p<0.05) when compared to rest of the sub-plot treatments. The weed competition negatively affected the tomato yield (Y=-0.7551X+7.88; R2=0.58; p<0.05), with Parthenium weed playing a dominant role. Mulching with G. sepium coupled with manual weeding during land preparation or ploughing would suppress growth and development of weeds including P. hysterophorus and enhance yield of tomato.
Keywords: Partheniumhysterophorus; Solanum lycopersicum; Weed Competition; Weed Control; Tomato Yield